If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3n + -16 = 7(n + 2) Reorder the terms: -16 + -3n = 7(n + 2) Reorder the terms: -16 + -3n = 7(2 + n) -16 + -3n = (2 * 7 + n * 7) -16 + -3n = (14 + 7n) Solving -16 + -3n = 14 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. -16 + -3n + -7n = 14 + 7n + -7n Combine like terms: -3n + -7n = -10n -16 + -10n = 14 + 7n + -7n Combine like terms: 7n + -7n = 0 -16 + -10n = 14 + 0 -16 + -10n = 14 Add '16' to each side of the equation. -16 + 16 + -10n = 14 + 16 Combine like terms: -16 + 16 = 0 0 + -10n = 14 + 16 -10n = 14 + 16 Combine like terms: 14 + 16 = 30 -10n = 30 Divide each side by '-10'. n = -3 Simplifying n = -3
| -3(4x-15)-8(3x-5)= | | 5d-2-d= | | -4y-8y=-15 | | 9x=9x+18 | | 9y=-1 | | 35+8r=7(2r-1) | | 5x-6=5x-x | | 6-x=-24 | | 3w-5-19w^2+17= | | 8(v+1)-4v=2(2v+2)-8 | | -5(1-5x)=-8x-5 | | 3+25+15x=58 | | 8y+4-6y=7+y-6 | | 2.4p-5=9.4 | | -6v-5(v+5)=-6v-5 | | 6-3x=5x-10x+4+2 | | 23=x^2+7 | | 13x+8x=3x-2 | | 8n+48=48+8n | | 6x+6=p | | -38-8n=-8(n+6)+2n | | y(5y^2+9)-2(7y-6y^3)= | | .2c+.286=2-.143c | | -6+2a=-6(a+5) | | -3(8x-27)-2(x+19)= | | -32+3r=7-4(7r+2) | | q-15=20 | | 4n-(3n+6)=-1 | | 16-a=-4(6a+1)+3a | | 21x-2=18x+30 | | -7(7+5b)=23+b | | 12n=12 |